Anti-HPA-1b Mediated Posttransfusion Purpura: A Case Report - O. P. Arewa; S. Nahirniak; G. Clarke (Case Reports in Medicine)
Posttransfusion purpura (PTP) is an uncommon, but potentially fatal, transfusion reaction characterized by profound thrombocytopenia and bleeding. PTP is caused by alloimmunization to human platelet specific antigens following blood component transfusion. Although there is evidence of a wide serological spectrum of culprit antibodies implicated, Anti-human-platelet-antigen- (HPA-) 1a is the most common antibody in cases reported. We report a case of posttransfusion purpura in an African American. The patient was negative for HPA-1a antibodies, but anti-HPA-1b was identified with a platelet phenotype of HPA-1a/HPA-1a. Although less common, HPA-1b antibody may be an important consideration in posttransfusion purpura diagnosed in patients of African descent.